1991
DOI: 10.1128/aem.57.2.426-433.1991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of a soil population of nonsymbiotic Rhizobium leguminosarum

Abstract: The genetic structure of a population of nonsymbiotic Rhizobium leguminosarum strains was determined by the electrophoretic mobilities of eight metabolic enzymes. Nonsymbiotic strains were isolated from the rhizosphere of bean plants and characterized by growth on differential media and at different temperatures, intrinsic antibiotic resistances, the lack of homology to a nijH probe, and their inability to form nodules on bean roots. All the isolates clustered with R. leguminosarum bv. phaseoli reference strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(98 citation statements)
references
References 25 publications
6
87
1
3
Order By: Relevance
“…Such patterns have a potentially simple mechanistic explanation in that several studies have reported the loss of mutualistic effectiveness in rhizobia via rapid evolution. In some cases this has been demonstrated to be associated with either the gain or loss of symbiosis-related genes carried on plasmids (Segovia et al 1991;Nandasena et al 2006;Crook et al 2012). Other clear examples of variation in rhizobial average effectiveness are strains with intermediate average effectiveness (e.g., strain CPI232) that are closely related to strains with high average effectiveness (e.g., strain CPI246).…”
Section: Discussionmentioning
confidence: 99%
“…Such patterns have a potentially simple mechanistic explanation in that several studies have reported the loss of mutualistic effectiveness in rhizobia via rapid evolution. In some cases this has been demonstrated to be associated with either the gain or loss of symbiosis-related genes carried on plasmids (Segovia et al 1991;Nandasena et al 2006;Crook et al 2012). Other clear examples of variation in rhizobial average effectiveness are strains with intermediate average effectiveness (e.g., strain CPI232) that are closely related to strains with high average effectiveness (e.g., strain CPI246).…”
Section: Discussionmentioning
confidence: 99%
“…phaseoli strain with the genetic capacity to fix N 2 in symbiosis is still considered a symbiotic strain when it is between hosts, in contrast to nonsymbiotic R. leguminosarum bv. phaseoli strains, which are unable to infect legumes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the work published about rhizobia, including a wide variety of publications about rhizobial diversity, is based on pure cultures obtained in this way. Due to the lack of reliable selection techniques, only a few studies are available analysing rhizobia that were isolated directly from soil and consequently did not undergo any competition or selection process through the host plant [1][2][3][4][5][6][7][8][9]. Some of these reports compared strains directly isolated from soil with strains selected by trap plants [4,8,9].…”
Section: Introductionmentioning
confidence: 99%